The Effect Of Service Quality and Promotion on Dimsum Purchasing Decisions at CV. Royal Insan Mandiri in Medan - Laksana, Ryan Dharmawan; Nasution, Amrin Mulia Utama (Economics, Business and Management Science Journal, 2024)
This study aims to determine “The Effect of Service Quality and Promotion on Dimsum Purchasing Decisions at CV. Royal Insan Mandiri in Medan”. This type of research is an associative and quantitative approach. The population in this study was 101 consumers using the Slovin formula technique, so the number of samples in this study was 50 respondents taken from part of the population. Based on the t-test of service quality with a value of tcount ttable (3,317 1,677) with a significant level of 0.002 0.05, then the promotion variable obtained tcount ttable(7,125 1,677). Partial positive and significant effect on dim sum purchasing decisions at CV. Royal Insan Mandiri. The value of Fcount28,680 is greater than Ftable of 3.19 with sig 0.0000.05, indicating that Ho is rejected and Ha is accepted. So, it can be concluded that the variable service quality and promotion together have a positive and significant effect on dim sum purchasing decisions at CV. Royal Insan Mandiri. The coefficient of determination (KD) = R2 X 100%, to obtain KD = 0.530%. This figure shows that 53% of purchasing decisions (dependent variable) can be explained by variables of service quality and promotion. The remaining 47% is influenced by other factors that are not explained in this study.